The Effect of Loan Market Concentration on Banking Rentability: A Study of Indonesian Commercial Banking, Dynamics Panel Data Regression Approach - Jumono, Sapto; Achsani, Noer Azam; Hakim, Dedi Budiman; Fidaus, Muhammad (International Journal of Economics and Financial Issues, 2016)
The aim of this research is to find out the speed of adjustment and impact of market concentration on rentability (Return on Equity). From 145 banks, there were 97 banks chosen in a period of 2001-2012 as sampling of research by using purposive sampling. This research uses data panel, therefore dynamics panel data regression is used in this research and using GMM Arellano Bonds as research tools. This research shows that speed of adjustment close to zero point which means the market condition is more competitive; and the variables which affect ROE are ROElag1, market concentration, bank size, non-performing loan, and overhead to revenue ratio meanwhile the other variables do not impact ROE Keywords: market structure, market share, ROE, banking industry, performance JEL Classifications: C23; G21; L11